2008
DOI: 10.1096/fj.08-112680
|View full text |Cite
|
Sign up to set email alerts
|

Calcium pentosan polysulfate is a multifaceted exosite inhibitor of aggrecanases

Abstract: Degradation of the cartilage proteoglycan aggrecan is a key early event in the development of osteoarthritis. Adamalysin with thrombospondin motifs (ADAMTS) -4 and ADAMTS-5 are considered to be the main enzymes responsible for aggrecan breakdown, making them attractive drugs targets. Here we show that calcium pentosan polysulfate (CaPPS), a chemically sulfated xylanopyranose from beechwood, is a multifaceted exosite inhibitor of the aggrecanases and protects cartilage against aggrecan degradation. CaPPS intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
138
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 106 publications
(145 citation statements)
references
References 48 publications
5
138
1
1
Order By: Relevance
“…We reported previously that TIMP-3 accumulated in the conditioned medium of HTB94 cells in the presence of RAP, an antagonist of ligand binding to the LRP family of endocytic receptors (18). In line with this finding, RAP (500 nM) reduced endocytosis of [ 35 S]TIMP-3 by HTB94 cells, i.e.…”
Section: Timp-3 Is Endocytosed By Htb94 Cells-metabolicallysupporting
confidence: 78%
See 3 more Smart Citations
“…We reported previously that TIMP-3 accumulated in the conditioned medium of HTB94 cells in the presence of RAP, an antagonist of ligand binding to the LRP family of endocytic receptors (18). In line with this finding, RAP (500 nM) reduced endocytosis of [ 35 S]TIMP-3 by HTB94 cells, i.e.…”
Section: Timp-3 Is Endocytosed By Htb94 Cells-metabolicallysupporting
confidence: 78%
“…We previously reported that levels of this physiologically and pathologically important inhibitor can be post-translationally regulated by endocytosis (18). TIMP-3 accumulates in the medium of HTB94 chondrosarcoma cells and porcine articular chondrocytes treated with receptorassociated protein (RAP), an antagonist of ligand binding to the LRP family of endocytic receptors (18). Using radiolabeled TIMP-3 we investigated the kinetics of TIMP-3 endocytosis and degradation by LRP-1-deficient PEA-13 mouse embryonic fibroblasts and their wild-type counterpart.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24,43 Apart from its antiinflammatory properties, 8,9,40,41,71,72,85 PPS is a potent leukocyte elastase 4 and aggrecanase (ADAMTS-4 and ADAMTS-5) inhibitor. [77][78][79][80] Pentosan polysulfate has been shown to mediate part of its antiinflammatory effects by downregulating TNF-a activity via the suppression of NF-Kb nuclear translocation and inhibition of the MAPKs pathways. 75,76,85 Since the levels of TNF-a 68 and ADAMTS-4/ADAMTS-5 51 are elevated in degenerative discs and have been implicated in the degradation of disc PGs, the combination of PPS with MPCs in the present study offered several potential advantages over the use of MPCs alone.…”
Section: Discussionmentioning
confidence: 99%